Photoluminescence quenching mechanisms in GaInNAs/GaAs quantum well grown by solid source molecular beam epitaxy - Ng, T. K. (2013)
The photoluminescence (PL) quenching characteristics of a thermal-annealed ~7 nm GaInNAs/ GaAs quantum well (QW) with In=30% and N=1.5% were studied from 4 to 150 K. It is found that the integrated PL intensity versus temperature characteristic can be well fitted by a double activation energy model. One of the centers with low activation energy EB=9 meV is thought to originate from a localized state that traps carriers at temperatures below ~100 K. Therefore, EB is the thermal energy required to activate the localized state carriers to the e1 state of the GaInNAs QW. Another center with larger activation energy EA=38 meV has a more significant PL quenching effect at temperatures above ~120 K. This center is possibly contributed by the EL6 defect level in the GaAs barrier layer, as a result of low V/III ratio of 15, and low growth temperature of 450 °C.